Labridae of the Red Book of Ukraine. Thematic bibliography - Ir. Hrytsyniak; T. Shvets (Ribogospodarsʹka Nauka Ukraïni)
Purpose. To create a thematic bibliographic list of publications, which highlight the results of scientific research of the family Labridae listed in the Red Book of Ukraine (2009): the goldsinny wrasse Ctenolabrus rupestris (Linnaeus, 1758) – a conservation status of rare species, the green wrasse Labrus viridis (Linnaeus, 1758) – a rare, very vulnerable species, and the longnoused wrasse Symphodus rostratus (Bloch, 1791) as a vulnerable species of the ichthyofauna of Ukraine.